Clinical pharmacist interventions in nutrition-and drug-related problems in critically ill patients with renal dysfunction: a non-randomized controlled study - Özgan, Betül; Ayhan, Yunus Emre; Apikoglu, Sule; Karakurt, Sait (Frontiers in Medicine, 2024)
Background: Critically ill intensive care unit (ICU) patients often face life-threatening drugrelated problems (DRPs) and malnutrition. Clinical pharmacists (CPs) play a crucial role in mitigating these issues and improving outcomes. Aim: This study was designed to detect, prevent, reduce or resolve nutrition-related problems (NRPs) and DRPs in intensive care patients with renal dysfunction through clinical pharmacy services. Method: This 9-month, prospective, non-randomized, controlled study was conducted in the ICU. During the intervention period (IP), CP recommendations addressing NRPs and DRPs were provided to the healthcare team. NRPs were evaluated using an expert-developed enteral nutrition consensus protocol, while DRPs were classified according to the Pharmaceutical Care Network Europe (PCNE) Classification for Drug-Related Problems Version 9.1. Result: The study included 60 patients with a median age of 73 years (IQR: 60.5-80). A total of 504 DRPs (8.4 per patient) were identified across all patients. DRPs were decreased by 50% during the IP compared to the observation period (OP) (p<0.001). The most common causes of DRPs were 'too low a drug dose' (22.2%), 'drug-drug interactions' (17%), and 'too high a drug dose' (16.4%). Of the recommendations made to the prescribing physician, 140 (97.9%) were accepted. In the IP, targeted calorie and protein supplementation was fully achieved in more patients (p<0.05). The most common recommendations included 'changes in the rate of nutrition' (66.7%), 'vitamin supplementation' (16.7%), and 'changes in enteral nutrition products' (7.7%). Conclusion: This study highlights the high incidence of DRPs and malnutrition risk in ICU patients with renal dysfunction, emphasizing the vital role of clinical pharmacists. Their collaboration with healthcare professionals significantly reduced both DRPs and NRPs.